Abatement of toxicity of effluents containing Cr(VI) by heterogeneous photocatalysis. Toxicity assessment by AMPHITOX assay - Hojman, Jonatan Y. (2015)
Toxicity of a Cr(VI) solution before and after treatment by TiO2 heterogeneous photocatalysis (HP) was performed with AMPHITOX bioassay. Changes in toxicity on Rhinella arenarum larvae for 10-d were monitored after exposure to an untreated Cr(VI) solution and to the same solution after HP treatment. The HP treatment of a 41.60 mg L−1 Cr(VI) solution reduced to 37.5% the concentration of the metal ion. A 10-fold reduction in toxicity at acute exposure (72 h) and 150-fold reduction in toxicity after 240 h was found. Further, the LOEC value increased from 0.001% for the untreated solution to 0.153% after HP treatment. Moreover, the safe concentration in untreated solution corresponded to 0.0001% sample, and it was 0.01% after the treatment, i.e., 100 times higher. A saving of water of about 100,000 L per L of effluent would be possible through dilution to allow safer concentrations for discharge; the saving would reach the highest value (1,000,000 L per L) at 240 h. Sub-lethal effects were completely absent in larvae exposed to the treated solution. The AMPHITOX test allowed to detect chronic effects at low Cr concentrations, i.e. at environmentally relevant levels.